PENGARUH KESADARAN WAJIB PAJAK, KEPATUHAN WAJIB PAJAK, KEBIJAKAN INSENTIF PAJAK DAN PELAYANAN FISKUS TERHADAP PENERIMAAN PAJAK DI MASA PANDEMI COVID-19 (STUDI KASUS DI KPP PRATAMA TULUNGAGUNG) - Rya Rahma Lutvitasari; Maslichah Maslichah; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The current COVID-19 pandemic has had an impact on the tax sector. Where the tax authorities must make breakthroughs and the right policies to optimize tax revenues. The purpose of this study was to determine the effect of Taxpayer Awareness, Taxpayer Compliance, Tax Incentive Policies and Fiscal Services on Tax Revenue during the Covid-19 Pandemic Period at KPP Pratama Tulungagung. This type of research is field research, using a quantitative approach. The data collection technique used primary data in the form of a questionnaire. The population used is individual taxpayers who are business actors or categorized as MSMEs registered at KPP Pratama Tulungagung. Samples were taken using the Slovin formula. The method used is multiple linear regression analysis, as well as partial or simultaneous hypothesis testing to determine the effect of each variable. The results showed that taxpayer awareness had no effect on tax revenues during the COVID-19 pandemic, while taxpayer compliance, tax incentive policies and tax service services had an effect on tax revenues during the COVID-19 pandemic.Keywords: taxpayer awareness, taxpayer compliance, tax incentive policy, tax service, tax revenue